Mesoporous Ni@C hybrids for a high energy aqueous asymmetric supercapacitor device. Issue 24 (7th June 2016) - An, Cuihua; Wang, Yijing; Jiao, Lifang; Yuan, Huatang
Abstract : In situ synthesized 1D Ni@C hybrids assembled by numerous core-shell-like Ni@C nanoparticles exhibited enhanced electrochemical performance as an aqueous asymmetric supercapacitor device. Abstract : An advanced asymmetric supercapacitor device (ASC) with high energy density was successfully fabricated by using a three-dimensional (3D) core–shell Ni@C hybrid as the positive electrode and activated carbon (AC) as the negative electrode. In addition, the Ni@C hybrid exhibited a one-dimensional (1D) morphology as a whole and a 3D core–shell nanostructure in details. The Ni@C hybrid was subtly controlled down to 10 nm scale to achieve a large exposed exterior surface and a remitting diffusion-controlled ion transference process. Moreover, the 1D porous texture and Ni-decoration of the Ni@C hybrids improved the supercapacitive performance enormously, with an ultrathin carbon shell ensuring a large external active surface and high electrical conductivity. Due to its unique core–shell structure, the Ni@C hybrid electrode delivered a high 2006 F g −1 capacitance at 1 A g −1, and still retained a high 1582 F g −1 capacitance with the current density increasing up to 20 A g −1 . Coupled with the AC negative electrode, the ASC device delivered a 152.7 F g −1 capacitance at 1 A g −1 and 99 F g −1 at 10 A g −1 . The capacitance retention reached up to 91% after 2000 cycles at a 1 A g −1 current density. In addition, the ASC device delivered a maximum 61.3 W h kg −1 energy density with a 1.6 V operational voltage, which could remain at 39.8 W h kg −1 even at a 1.12 kW kg −1 power density, suggesting promising future applications.